Efektivitas dan Mekanisme Biokimia Batang Pisang sebagai Media Biofilter pada Pengolahan Efluen Septic Tank: Sebuah Tinjauan Sistematis - Darwis Baso (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Septic tank effluent treatment remains a challenge in decentralized sanitation systems, due to technological and cost constraints. Biomass-based natural biofilter media, such as banana stem, have increasingly been investigated as low-cost, environmentally friendly, and easily applicable alternatives. This study aims to systematically review the use of banana stem as a natural biofilter for septic tank wastewater treatment, focusing on study characteristics, treatment performance, process mechanisms, and factors determining efficiency and performance variability. The study was carried out using the literature review method approach following the PRISMA protocol, covering peer-reviewed articles published between 2021-2025. The results show that banana stem media can achieve removal efficiencies of 60-85% for Total Suspended Solids (TSS), 45-80% for Chemical Oxygen Demand (COD), and 50-77% for Biochemical Oxygen Demand (BOD), with optimal performance at a Hydraulic Retention Time (HRT) of 12-24 hours. The porous structure and lignocellulosic content promote rapid microbial biofilm formation, although performance variability is influenced by organic loading fluctuations and media degradation. Overall, banana stem has strong potential as an effective, economical, and sustainable natural biofilter for decentralized sanitation systems.